2023
DOI: 10.1038/s41467-023-38218-w
|View full text |Cite
|
Sign up to set email alerts
|

N-Formimidoylation/-iminoacetylation modification in aminoglycosides requires FAD-dependent and ligand-protein NOS bridge dual chemistry

Abstract: Oxidized cysteine residues are highly reactive and can form functional covalent conjugates, of which the allosteric redox switch formed by the lysine-cysteine NOS bridge is an example. Here, we report a noncanonical FAD-dependent enzyme Orf1 that adds a glycine-derived N-formimidoyl group to glycinothricin to form the antibiotic BD-12. X-ray crystallography was used to investigate this complex enzymatic process, which showed Orf1 has two substrate-binding sites that sit 13.5 Å apart unlike canonical FAD-depend… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The naturally occurring streptothricin analog BD-12 contains a formimidoylglycine group in place of β-lysine(s), notably lacking the β-amino group targeted by streptothricin acetyltransferases 48 . Neither in vitro reactions between BD-12 and a streptothricin acetyltransferase nor the aminoglycoside modifying enzyme AAC(6')-Ie-APH(6")-Ia resulted in an acetylated product, suggesting BD-12 may avoid inactivation by acetylating resistance enzymes 124 . Additional streptothricin derivatives with unnatural β-lysine modifications have been prepared through enzymatic modification in vitro, including replacement of β-lysine by 3-aminoproprionyl, 4-aminobutyl, or β-homolysine groups 124,125 .…”
Section: Bacterial Streptothricin Resistance Mechanisms and Determina...mentioning
confidence: 95%
See 1 more Smart Citation
“…The naturally occurring streptothricin analog BD-12 contains a formimidoylglycine group in place of β-lysine(s), notably lacking the β-amino group targeted by streptothricin acetyltransferases 48 . Neither in vitro reactions between BD-12 and a streptothricin acetyltransferase nor the aminoglycoside modifying enzyme AAC(6')-Ie-APH(6")-Ia resulted in an acetylated product, suggesting BD-12 may avoid inactivation by acetylating resistance enzymes 124 . Additional streptothricin derivatives with unnatural β-lysine modifications have been prepared through enzymatic modification in vitro, including replacement of β-lysine by 3-aminoproprionyl, 4-aminobutyl, or β-homolysine groups 124,125 .…”
Section: Bacterial Streptothricin Resistance Mechanisms and Determina...mentioning
confidence: 95%
“…Neither in vitro reactions between BD-12 and a streptothricin acetyltransferase nor the aminoglycoside modifying enzyme AAC(6')-Ie-APH(6")-Ia resulted in an acetylated product, suggesting BD-12 may avoid inactivation by acetylating resistance enzymes 124 . Additional streptothricin derivatives with unnatural β-lysine modifications have been prepared through enzymatic modification in vitro, including replacement of β-lysine by 3-aminoproprionyl, 4-aminobutyl, or β-homolysine groups 124,125 . Many of these streptothricin analogs have lower antimicrobial activity compared to the canonical streptothricins, suggesting that incorporating residues more similar to β-lysine, such as N-methylated ones, could potentially retain amineribosome electrostatic interactions necessary for high levels of antimicrobial activity (with ribose O2' groups at positions U1052 and C1054 16 ) while avoiding disruptive acetylation by resistance enzymes (Fig.…”
Section: Bacterial Streptothricin Resistance Mechanisms and Determina...mentioning
confidence: 95%
“… 26 A more recent study showed that Orf1, which is involved in the biosynthesis of BD-12, contains an N–O–S bridge that plays an important role in catalysis. 27 Orf1 is a noncanonical FAD-dependent enzyme responsible for appending a glycine-derived N -formimidoyl group to glycinothricin, producing the antibiotic BD-12. The X-ray crystallographic analysis revealed that Orf1 forms an oximinoglycine with an N–O–S–Cys281 substrate–enzyme bridge, which mediates the nucleophilic addition of glycinothricin and decarboxylation, leading to the cleavage of the N–O bond and the production of a formimidoylated final product.…”
Section: Cysteine Dioxygenase (Cdo)mentioning
confidence: 99%
“…The X-ray crystallographic analysis revealed that Orf1 forms an oximinoglycine with an N–O–S–Cys281 substrate–enzyme bridge, which mediates the nucleophilic addition of glycinothricin and decarboxylation, leading to the cleavage of the N–O bond and the production of a formimidoylated final product. 27 …”
Section: Cysteine Dioxygenase (Cdo)mentioning
confidence: 99%